1983
DOI: 10.1254/jjp.33.1145
|View full text |Cite
|
Sign up to set email alerts
|

Crescentic type nephritis induced by anti-glomerular basement membrane (GBM) serum in rats.

Abstract: Abstract-An experimental model of crescentic type nephritis was established by im munizing rats that had been given at i.v. nephritogenic dose (0.4 ml/animal) of rabbit anti-rat glomerular basement membrane (GBM) serum [anti-GBM serum] with 5 mg of rabbit r-globulin in Freund's complete adjuvant, and the process of nephritis was in vestigated by means of biochemical, histopathological and immunopathological analyses. Rats treated with anti-GBM serum and then with rabbit r-globulin (group II) showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 9 publications
0
17
2
Order By: Relevance
“…Our previous study indicated that immunization with rabbit r-G following i.v. injection of rabbit anti GBM serum to rats caused severe glomerular injury, which led to extensive formation of crescents by enhancing the immune response in the autologous phase via the persistent formation of the host antibody against rabbit r-G (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study indicated that immunization with rabbit r-G following i.v. injection of rabbit anti GBM serum to rats caused severe glomerular injury, which led to extensive formation of crescents by enhancing the immune response in the autologous phase via the persistent formation of the host antibody against rabbit r-G (6).…”
Section: Discussionmentioning
confidence: 99%
“…injection of 1.0 ml of rabbit anti rat GBM serum into the tail vein in accordance with the method reported previously (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Induction of crescentic-type anti-GBM nephritis Crescentic-type anti-GBM nephritis was inducted by immunizing rats that had received a nephritogenic dose of rabbit anti-rat GBM (anti-GBM) serum with rabbit y globulin (rgG) according to a slight modification of the previously reported method (8). Fifty rats weighing approx.…”
Section: Drugsmentioning
confidence: 99%
“…To elucidate the antinephritic actions and mecha nisms of OB-5 in an experimental model of rapidly progressive glomerulonephritis, we investigated the effects of OB-5 on crescentic-type anti-GBM nephritis, which has more severe proteinuria and proliferation of glomerular cells than those of the original-type model (8). In addition, we undertook studies utilizing mono clonal antibody against total leukocytes (OX-1), macro phages (ED-1), cytotoxic/suppressor T cell (OX-8), la positive cells (RT1B) and IL-2 positive cells (OX-39) to detect the effect of OB-5 on the number of these cells in the glomeruli of nephritic rats.…”
mentioning
confidence: 99%